Penyaringan Ketahanan Jalur Haploid Ganda Padi Gogo Hasil Kultur Antera Terhadap Penyakit Blas Daun - Bakhtiar Bakhtiar; Bambang S Purwoko; Mukelar Amir (Fakultas Pertanian, Universitas Syiah Kuala, 2009)
Screening of Doubled Haploid Lines Derived from Anther Culture of Upland Rice to Leaf Blast DiseaseABSTRACT. Rice blast disease caused by Pyricularia grisea (cooke) Sacc, is one of limiting factors to increase upland rice production. Many resistant varieties have been developed, but they have become susceptible within a few years after their release. Breeding for blast disease resistance should be done continuously. This study was conducted in Laboratory and Screenhouse at ICABIOGARD, Bogor. Preparation of rice seedlings and inoculums, inoculation technique and scoring system were done according to standard procedures established by IRRI. The evaluation of doubled haploid lines showed that SGJT3, SGJT16, SGJT28, SGJT29, SGJT34, SGGM5, SGGM8, GRGM9, and GRJT12 lines were resistant to leaf blast disease race 173, 033, and 001.